The role of the military in combating human trafficking: A South African perspective - Mollema, Nina (Scientia Militaria - South African Journal of Military Studies, 2017)
Human trafficking is a complex and diverse crime affecting both individuals and countries across the world. As a significant facet of transnational organised crime and one of the most lucrative criminal enterprises globally, human trafficking was ranked in 2015 as the second most profitable crime around the world, making it the fastest-growing source of revenue for organised criminal operations internationally. In 2015 South Africa implemented comprehensive anti-trafficking legislation. Before such legislation was enacted, the South African government also ratified several international and regional human-rights instruments in terms of which specific duties are imposed upon the state to effectively combat and punish the crime including the protection of the rights of victims. The focus of this article is the desired role of the military in combating human trafficking in South Africa. In 2004, the North Atlantic Treaty Organisation adopted a Policy on Combating Trafficking in Human Beings of 2004. The policy sets out various strategies for ensuring regional co-operation in combating human trafficking. It is suggested that the South African National Defence Force takes the initiative in formulating a similar policy in order to effect better co-operation amongst nation states in Africa, especially in the southern region of Africa, to combat human trafficking. In order to meaningfully address the role of the Defence Force in the fight against human trafficking and to develop evidence-based strategies and policies, regional coordination in combating trafficking is paramount. This article will examine current legislation, instruments and strategies as regards human trafficking in order to make further recommendations for counter-trafficking policy standards and best practices for the South African National Defence Force.